Peedanil Gold, Herbo-Mineral Formulation, Moderates Cytokine Levels and Attenuates Pathophysiology in Monosodium Iodoacetate Induced Osteoarthritis in SD Rat Model - Balkrishna, Acharya; Sinha, Sandeep; Karumuri, Shadrak; Srivastava, Jyotish; Haldar, Swati; Varshney, Anurag (Frontiers in Pharmacology, 2022)
The inflammatory cartilaginous degeneration of the articular joints, mostly those of knee, hips and hands, is osteoarthritis (OA). The available treatment strategies for osteoarthritis are designed for pain relief, molecular targeting, cartilage regeneration and surgical intervention. However, meta-analysis of clinical trials has shown these strategies to be sub-optimal, thereby, eliciting a need for investigating alternative options. The herbo-mineral formulation, Peedanil Gold (PN-G) has been used against joint pains and inflammation. In the current study, anti-osteoarthritic effects of PN-G were investigated in rat model of OA, induced by intra-articular injection of monosodium-iodoacetate. PN-G treatment improved the clinical and Kellgren & Lawrence scores; and rescued the osteoarthritic rats from hyperalgesia and allodynia. Besides, PN-G treatment ameliorated joint inflammation and abrogated in vivo osteoarthritic pathology through effective cartilage regeneration, measured radiologically and histopathologically. PN-G also reduced the levels of interleukin-6 (IL-6) and interleukin -1 beta (IL-1β), in a dose dependent manner, in inflamed human macrophagic THP-1 cells, thereby, reaffirming its anti-inflammatory property at cytosafe concentrations. High performance liquid chromatography (HPLC) revealed the presence of several analgesic and anti-inflammatory phytocompounds, ellagic acid, guggulsterone E, guggulsterone Z, 5-(hydroxymethyl) furfural, corilagin, cinnamic acid, ferulic acid, gallic acid and protocatechuic acid in PN-G. In conclusion, this study has succinctly demonstrated that PN-G is capable of relieving the clinical symptoms of osteoarthritis, which is measurable through the established osteoarthritic serum biomarker, Cartilage Oligomeric Matrix Protein (COMP).